Gallic acid ameliorates dextran sulfate sodium-induced ulcerative colitis in mice via inhibiting NLRP3 inflammasome - Yu, Tian-Yuan; Feng, Yi-Ming; Kong, Wei-Song; Li, Shan-Ni; Sun, Xue-Jiao; Zhou, Gui; Xie, Rui-Fang; Zhou, Xin (Frontiers in Pharmacology, 2023)
Background: Ulcerative colitis (UC) is a chronic recurrent inflammatory bowel disease (IBD). The conventional drugs for UC may induce severe side effects. Herbal medicine is considered as a complementary and alternative choice for UC. Purpose: This study aims to estimate the effect of natural polyphenol gallic acid (GA) on the NLRP3 inflammasome with dextran sulfate sodium (DSS)-induced colitis in mice. Study design: The body weights and symptoms of BALB/c mice were recorded. Histological evaluation, ELISA, q-PCR, immunohistochemistry, and western blotting were carried out to observe the morphology, cytokine contents, mRNA expressions, and protein expressions, respectively. Lipopolysaccharide (LPS)-induced RAW264.7 macrophage was used to probe GA’s effect on relative protein expression. Results: GA attenuated weight loss (p < 0.05), relieved symptoms, and ameliorated colonic morphological injury (p < 0.05) in mice with colitis induced by DSS. GA also lowered the contents of TNF-α, IL-1β, IL-18, IL-33, and IFN-γ in the serum and colon of mice, which were elevated by DSS, downregulated protein, and mRNA expressions of the NLRP3 pathway in the colon tissue. Furthermore, GA downregulated the expressions of NLRP3 (p < 0.05), iNOS (p < 0.01), COX2 (p < 0.01), and P-p65 (p < 0.05), and suppressed NO release (p < 0.001) in LPS-induced RAW264.7 cells. Conclusion: GA ameliorated DSS-induced UC in mice via inhibiting the NLRP3 inflammasome. These findings furnish evidence for the anti-inflammatory effect of herbal medicines containing GA on UC.